Structural Linguistics and Modern Linguistics - Alpatov, Michajlovic Vladimir (Bohemica Olomucensia, 2016)
The article outlines the structural period (usually spanning 1916 through 1957) in the history of the world linguistics while emphasizing its importance in the study of Slavic languages, especially Czech and Russian. Despite the fact that the structural epoch finished and was replaced by modern language theories its methods are still in use. Many of its terms and notions (functions, oppositions, neutralization of oppositions, etc.) are used by linguists of different schools and thus continue developing. The ideas of the Prague school and American descriptive linguistics are especially significant.
Keywords: Ferdinand de Saussure; structuralism; the Prague school; American descriptive linguistic